La fuerza de trabajo es una mercancía...The labor force is a commodity... - García López, Jorge (Cuadernos de Relaciones Laborales, 2003)
The labour force is a commodity... this does not imply that the social (wage) relations that determine it as such become a less sociological subject of study. This is the principle from which we are trying to approach a critical evaluation of the two topical theoretical frameworks used in the field of the labour relations studies: the sociology of work and the sociology of employment. Moreover, to try and undertake this evaluation implies a systematic comparison between these two theoretical frameworks within a context marked nowadays by the virtuality of this confrontation in our country. First, we will establish the axes that, from our point of view, define the analytical spaces and explanation procedures of the work and employment’s theoretical frameworks. Secondly, after two critical readings, we will propose a different sociological approach: to place the market oriented nature of the labour force in the core of another theoretical framework whose aim is focused neither in work nor in employment, but in wage relations’ social and historical base.
Keywords: Wage Relations; Sociology of Work; Sociology of Employment